Reassessment of multiple species of Gymnelus (Teleostei: Zoarcidae) in Pacific Arctic and boreal regions - Mecklenburg, Catherine W.; Anderson, M. Eric (Zootaxa, 2015)
Recently described new nominal species and resurrected species in the eelpout genus Gymnelus Reinhardt 1834 were reassessed for validity using fresh material collected in Pacific Arctic regions and a large body of data from a previous systematic review of the genus. The analysis reported here included both DNA barcodes and morphology. Only two species were validated: G. viridis (Fabricius 1780) and G. hemifasciatus Andriashev 1937. The latter species occurred as two morphotypes for which there is some evidence of difference in ecological preference, but the available environ-mental data are not robust enough to firmly identify or verify ecophenotypes.